The determinants of managerial decisions under risk - Martin G. Kocher; Ganna Pogrebna; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2008)
In hierarchical organizations the role of a team leader often requires making decisions which do not necessarily coincide with the majority opinion of the team. However, these decisions are final and binding for all team members. We study experimentally why, and under which conditions, leaders resort to such decisions. In our experiment, teams are presented with several paired lottery choices. They decide by majority voting which lottery from the lottery pair they prefer to be played out. After all members of the team have made their choices, the team leader is informed about the outcome of the vote and has an opportunity either to confirm or to alter the majority decision. We find that leaders overrule their teams in 35% of cases and such decisions are primarily driven by divergent preferences of leaders and the other team members. Male, younger and more risk seeking (as opposed to female, older and more risk averse) leaders overrule decisions of ordinary team members more often. We discuss the implications of our findings for the management of organizations.
Keywords: C91; C92; D91; M14; 330; leadership; risk attitude; managerial decisions; collective choice; choice under risk; Entscheidung bei Unsicherheit; Führungspersönlichkeit; Gruppenentscheidung; Risikopräferenz; Test